1992
DOI: 10.1161/01.hyp.19.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin stimulated by angiotensin II augments contractility of spontaneously hypertensive rat resistance arteries.

Abstract: In cultured endothelial cells, endothelin is produced after stimulation with angiotensin II. The effects of angiotensin II and endothelin-1 on vascular sensitivity to norepinephrine were studied in perfused rat mesenteric resistance arteries. Expression of endothelin messenger RNA (mRNA) was determined in endothelial cells obtained from the mesenteric circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
1
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(117 citation statements)
references
References 32 publications
8
106
1
2
Order By: Relevance
“…37 In cultured endothelial cells, Ang II may increase the release of ET-1. 38 In the present study, significant increased systemic venous levels of ACE activities were found in psychogenic and organogenic ED subgroups compared to controls. In addition, the cavernosal level of ACE activity was significantly higher in diabetic compared to psychogenic ED patients.…”
Section: Vasoactive Mediators and Erectile Dsyfunction E A Hamed Et Alsupporting
confidence: 57%
“…37 In cultured endothelial cells, Ang II may increase the release of ET-1. 38 In the present study, significant increased systemic venous levels of ACE activities were found in psychogenic and organogenic ED subgroups compared to controls. In addition, the cavernosal level of ACE activity was significantly higher in diabetic compared to psychogenic ED patients.…”
Section: Vasoactive Mediators and Erectile Dsyfunction E A Hamed Et Alsupporting
confidence: 57%
“…Pastore et al 14 demonstrated increased expression and plasma levels of cell adhesion molecule ICAM-1 with intravenous angiotensin II infusion. Furthermore, angiotensin II have been shown to stimulate production of endothelin-1 16 and plasminogen-activator inhibitor-1 17 in vivo. Increased ICAM-1 levels have recently been reported in patients with coronary artery disease and were regarded as an independent risk factor of myocardial infarction in patients with coronary artery disease 18 and in healthy males.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a positive correlation between ET-1 plasma level and systolic blood pressure in humans, 9 and the vascular production of ET-1 under angiotensin II (Ang II) stimulation is higher in hypertensive than in normotensive rats. 10 The amplification is nevertheless blocked by Ca 2+ entry blocker in human arteries 4 and in the rat mesenteric bed. 6 In contrast, the direct effect of ET-1 is relatively insensitive to Ca 2+ entry blockers.…”
Section: Camentioning
confidence: 97%